Association of Helicobacter Pylori Infection with Anemia: A Retrospective Study - Misbah Vaqar Patoli; Fasiha Sohail; Muhammad Fahad Zakir; Arfeen Azam Khan; Daara Jamali; Arzu Jadoon Khan (Liaquat National Journal of Primary Care, 2022)
Background: Helicobacter pylori (Hpylori) infection affects around half of the worlds’ population. Anemia is considered a complication of Hpylori infection. The present study aimed to determine the association of Hpylori infection with anemia in the Pakistani population. Methods: This retrospective observational study was conducted in Ziauddin University Hospital after taking ethical approval from the ethics committee. Medical records were reviewed for all those patients who investigated for helicobacter pylori infection and hematological parameters during 2020. Patients’ age, gender, residence, body mass index, presenting features, comorbidity, Hpylori status and other hematological parameters including hemoglobin (g/dL), packed cell volume (L/L), red blood cells (mcL), mean corpuscular volume (fL), mean corpuscular hemoglobin (pg) and mean corpuscular hemoglobin concentration (g/dL) were retrieved and analyzed. Results: A total of 370 records were reviewed. The median age of patients was 39 (IQR=27–50.3) years and the majority of them were females (54.6%). Nearly half of the participants had a helicobacter pylori infection (48.1%). Patients’ age (p=0.034), body mass index (p=0.048), gender (p=0.048) and symptom of heartburn (p=0.002) were significantly different among patients with and without Hpylori infection. 194 (52.4%) patients had anemia. The frequency of anemia among Hpylori positive and negative was 53.9% and 51% respectively. The risk of anemia was higher among Hpylori infected patients than non-infected patients but statistically, it was not significant (aOR=1.22, 95% CI: 0.79 - 1.86). The likelihood of microcytic hypochromic anemia was significantly higher in Hpylori infected patients than non-infected (aOR=1.78, 95% CI: 1.14 - 2.76). Conclusion: The present study did not find the association of Hpylori infection with anemia among the Pakistani population